English as an International Language Education Critical Intercultural Literacy Perspectives - Sahlane, Ahmed; Pritchard, Rosalind (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume provides an overview of current issues in English as an International Language (EIL) education and critical intercultural literacy pedagogy. The different chapters are inspired by 'critical interculturality' as a decolonial project that seeks to interrogate the structures, conditions, and mechanisms of colonial power relations that still pervade our increasingly globalising postcolonial societies; they tend to perpetuate forms of discrimination such as sexism, racism, classism, heterosexism and linguicism. Divided into five sections, this collection critically examines English Language Teaching textbooks' integration of intercultural dimensions, the promotion of intercultural literacy in teacher education programs, the management of cultural diversity in multicultural professional/business and educational situations, and the 'decolonisation' of the curriculum in various global educational and professional situations. The book presents a range of linguistic approaches as a means of examining the nature of intercultural communication pertaining in EIL varied international contexts. The chapters also reflect a wide diversity of perspectives from local contexts with global relevance and applicability. This book is an indispensable reference for business leaders, international relations stakeholders, education and linguistics students, educationists, textbook designers, teacher trainers and researchers of language and culture, critical pedagogy, multiculturalism studies, TESOL and English as a lingua franca (ELF).
Chapter 1: (De)Coloniality, Indigeneity and the Cultural Politics of English as an International Language: A Quest for then'Third Space' -- Part I: Intercultural Literacy in EIL Education: Towards a Post-Native Speakerist Approach -- Chapter 2: Critical Intercultural Language Teaching: Moving from Beliefs to Instructional Practices in EFL Classrooms -- Chapter 3: Promoting Intercultural Critical Literacy among Moroccan University Students through Online International Collaborative Education -- Chapter 4: The Transformation of an English User into an Intercultural English User -- Part II: Fostering a Culturally Responsive Pedagogy in Teacher Education -- Chapter 5: (En)Countering the 'White' Gaze: Native-speakerist Rhetorics and the Raciolinguistics of Hegemony -- Chapter 6: "I Wasn't Good Enough through Their Eyes":White Dominance and Conceptions of the "Good Teacher" in Teacher Education in Canada -- Chapter 7: Sensitising Teachers to Prejudices in Representations of Indigenous Peoples in EFL Textbooks -- Chapter 8: Building on and Sustaining Multilingual Children's Cultural and Linguistic Assets in Superdiverse Early Childhood Education -- Chapter 9: Challenging Invisibility in a Privileged Discourse Space: Culturally and Linguistically Inclusive University Teaching -- Chapter 10: Teacher - Culture - Pluri: An International Initiative to Develop Open Educational Resources for Pluralistic Teaching in FL Teacher Education -- Chapter 11: Teachers' Perceptions of Cultural Otherness in Sri Lanka:Bridging the Gap in ELT Interculturality -- Chapter 12: Pre-service Teachers' Difficulty Understanding English as a Lingua Franca for Intercultural Awareness Development -- Chapter 13: Re-envisioning EIL-informed TESOL Teacher-Education Curriculum -- Part III: Intercultural Communication, EIL Education and Diversity Management -- Chapter 14: Health Communication in Pakistan: Establishing Trust in Networked Multilingualism -- Chapter 15: Cultural Competency as a Critical Component of Quality Public Administration Services: A Model for Leading Multicultural Teams -- Chapter 16: Novice Multilingual Writers Learning to Write and Publish: An Intercultural Perspective -- Part IV: Intercultural Literacy Assessment in EIL Education -- Chapter 17: Assessing Perspectives on Culture in Saudi EFL Textbook Discourse -- Chapter 18: Gender and Visual Representation in Moroccan ELT Textbook Discourse -- Chapter 19: The Impact of English Proficiency on the Sociocultural and Academic Adaptation of Chinese Students in Short-term Exchange Programs: The Mediating Effects of Cultural Intelligence -- Part V: Decolonising Minds, Discourses and Practices -- Chapter 20: The Struggle to Decolonize English in School Curricula -- Chapter 21: Coloniality, Interculturality, and Modes of Arguing -- Chapter 22: Reconstructing Educational Administration and Leadership Language and Concepts for Teaching in the Arabian Gulf: Critical, Hermeneutic and Postcolonial Dimensions of Decolonising Curriculum -- Chapter 23: "She is not a Normal Teacher of English": Photovoice as a Decolonial Method to Study Queer Teacher Identity in Vietnam's English Language Teaching -- Chapter 24: Teaching EIL as a Tool of Social and Ideological Manipulation in South Korea: Does School and Student Socioeconomic Status Matter? -- Chapter 25: Intercultural Competence - a Never-ending Journey -- Chapter 26: Redefining EIL through Embracing Transcultural Ways of Knowing: Challenges, Opportunities, and Future Directions.
Keywords: Literacy; Language and languages -- Study and teaching; Inclusive education; Literacy; Language Education; Inclusive Education